THE IMPACT OF ARTIFICIAL INTELLIGENCE ON LANGUAGE TEACHING METHODOLOGY: OPPORTUNITIES AND LIMITATIONS - Shukurullo Burkhanov; Durdona Khamidova (Bright Mind Publishing, 2025)
Through the introduction of individualized and flexible learning experiences, artificial intelligence (AI) is changing the face of language instruction. Chatbots, virtual tutors, and speech recognition software are examples of AI-driven apps that give students personalized instruction and real-time feedback, improving their competency. This study looks at the advantages AI offers language teachers, such as increased student engagement, assessment automation, and individualized education. It also examines AI's drawbacks, including decreased human interaction, moral dilemmas, and prejudice in language recognition. This study offers insights into how AI might enhance conventional language teaching techniques to optimize learning results by examining recent research and practical applications.
Keywords: Artificial intelligence, language learning, teaching methodology, educational technology, personalization, machine learning, virtual tutors.